APPLICATION OF PATIENT SAFETY INCIDENT REPORTING SYSTEM IN HOSPITALS: LITERATURE REVIEW - Rumini; Purwarini, Justina (Jurnal Ilmiah Keperawatan, 2024)
Patient Safety Incident Reporting for improvement of the service system and prevention of recurring patient safety incidents is a very important part and affects the quality of service, so it is necessary to evaluate the implementation of the ICP reporting system at the hospital. Objective: To ascertain the elements that impact hospital patient safety event reporting.  Method: This article was written utilizing a literature review methodology. Data was gathered from database sources, and 20 articles between 2018 and 2023 were examined for PICOT analysis using the keywords patient safety incident, reporting, and health service. Results: There are three elements that affect the reporting of patient safety incidents that take place in hospitals: government, organizational, and human factors. It can be observed from features of nurse skills and patient safety culture in addition to environmental influences (individuals, organizations, and government). Cultural barriers (avoidance of conflict and fear of being blamed and penalized) and practical barriers (lack of expertise, so officers do not know how to report occurrences, lack of feedback, and lack of socialization connected to reporting incidents). Discussion: As a result of the existing literature review, no one has discussed the existence of organizational/hospital and government targets in efforts to achieve the target percentage (%) of PSI reporting. In order to improve employee motivation and involvement in reporting patient safety incidents and, ultimately, raise the standard of care provided to hospital patients, more research is required regarding the implementation of patient safety incident reporting in hospitals. Conclusion: The reporting of patient safety incidents in hospitals is influenced by three factors: personal, organizational, and governmental. Lack of feedback has been recognized as one of the weaknesses in incident reporting.